EFEKTIVITAS PENGOLAHAN LIMBAH CAIR DALAM MENURUNKAN KADAR FENOL DI RUMAH SAKIT UMUM DAERAH dr. ZAINOEL ABIDIN (RSUDZA) BANDA ACEH - Cut Yulvizar (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
The aims of this research were to determine the effectiveness of waste water processing in reducing content of phenol in RSUDZA. Research was conducted from June to September 2009. This research used 2 locations sampling which consist the tub before processing (inlet) and after processing (outlet), then data taken in 10 repetition consecutive days. The observed parameter ware phenol content and parameter like pH, BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand) dan TSS (Total Suspendid Solid) content. Data were analyzed by using paired t test (P0,05). The result show that fenol content were significant different before and after the processing. Phenol content decreased from 32% to 96.4%. Phenol content (0.020 mg/L) outlet had fulfilled the quality standard already established. These refer as judged effective values the pH parameters show that there were increasing. The result also show that not only phenol content decrease but also BOD, COD and TSS content.